Executives’ ESG cognition and enterprise green innovation: Evidence based on executives’ personal microblogs - Wang, Deli; Luo, Yonggen; Hu, Shiyang; Yang, Qi (Frontiers in Psychology, 2022)
Based on cognitive theory and high-order theory, this paper uses the data of listed manufacturing companies in China from 2010 to 2019 to study the impact of executives' ESG cognition on enterprise green innovation. Based on the data of corporate executives' personal microblogs, this paper quantifies the ESG cognition of corporate executives by using the method of text analysis. The results show that executives' ESG cognition significantly improves the level of green innovation of enterprises. In addition, after solving endogenous problems through a series of robustness tests, the conclusions of this paper are still valid. Further research shows that the promotion of ESG cognition of executives on the green innovation level of enterprises is mainly reflected in the samples with non-heavy pollution, low financing constraints and high marketization process. Based on the ESG cognitive perspective of executives, this study enriches the research of enterprise green innovation, and provides theoretical basis and practical reference for enterprise green innovation practice.